THE APPLICATION OF WEBTOON TO IMPROVE STUDENTS READING COMPREHENSION: A CASE OF SMPN 2 KARANGRAYUNG GROBOGAN IN THE ACADEMIC YEAR 2022/2023 - Claudya Sudaryanto; Indri Kustantinah; Siti Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research focuses on students’ problems related to their reading comprehension. This research tries to examine the use of Webtoon application media for ninth grade students at SMPN 2 Karangrayung Grobogan. The aim of this research is to find out whether there is significant difference between students who are taught using Webtoon application and students who are taught without using Webtoon application as a learning media in class. The aim of this research (1) To investigate the reading comprehension of students taught using Webtoon application. (2) To investigate the reading comprehension students taught using Webtoon application. (3) To find out the significant difference between those using and taught without using Webtoon application. In this research, researcher used quantitative and qualitative research design as the design of study, by recruiting 30 students from one class in class IX students of SMPN 2 Karangrayung Grobogan as research subject. The data collection methods used are pre-test, post-test, and observation. Based on the students’ pre-test and post-test results that have been distributed, it shows that the pre-test with a value of 55.1 and included in the poor category is higher than the post-test score with a value of 38.8 and included in the bad category. This shows that there is a significant difference between students who were taught without using Webtoon application getting high score while students who were taught using Webtoon application got lower scores. This is also in line with the statement given by students in the observations that have been given which state that most students are less motivated to improve their reading comprehension using the Webtoon application. Based on data analysis, researcher can conclude that the Webtoon application is less helpful in improve students’ reading comprehension in class IX of SMPN 2 Karangrayung Grobogan.